El desarrollo forestal sostenible en la Ley Forestal Y De Conservación De Áreas Naturales Y Vida Silvestre - Monteros Cueva, Alba Daniela (2015)
Ecuador is considered as one of the countries with more biodiversity of species in the world, that is why, even though it’s a small in territory, it has been recognized as the country with the most diversity per square mile in the planet. It’s privileged geographical location – with four natural regions – its varied setoffs and the influence of marine currents, allow the formation of different types of flora, fauna and microorganisms. That’s the reason of the need to protect the biological diversity, in order to avoid negative environmental impacts that can provoke catastrophic and disastrous phenomenon such as erosion, extinction of species, expansion of deserted areas, landslides, among others. This is the reason why, as an event without preceding, the Constitution of the Republic of Ecuador, promulgated in 2008, recognizes and guaranties nature’s rights, in article 396, it indicates that it’s a States duty to adopt proper politics and measures aimed to avoid negative environmental impacts. In other words, it’s the Ecuadorian States duty to take the necessary measures in order to preserve the Ecuadorian biodiversity, in which it includes national politics for a sustainable forest development and protection. Nowadays, the indiscriminate exploitation of forest resources represents a serious problem for the preservation of native forests; this is because erosion, deforestation and the loss of biodiversity is increasing more every day. That’s why people and companies that make a living out of this type of activities must know appropriate techniques that can help preserve biodiversity and avoid deforestation, desertification and soils erosion. For this, it’s necessary for the Ecuadorian State, to have an appropriate legislation that helps private land owners and wood industrials to take care of the environment or to be sanctioned in case they don’t carry out with the politics to preserve forest resources. It’s important to point out that even though the Ecuadorian Environmental Office carries out hard work to preserve biodiversity with programs like “Socio Bosque”, “Calidad Ambiental”, “Huella Ecológica”, “Conservación de la Biodiversidad Marino Costera del Ecuador”, among others; however they don’t show a citizen participation that allows the collectivity to make conscience in the need of taking care of forest in order to take part in the new era of environmental preservation. The need to create spaces of citizen integration is a must; considering the amount of the trees being cut down has increased because of the high demand of wood species that in many cases are sold in illegal markets. To this we add the fact that most Ecuadorians don’t have knowledge that the Forest Law conditions the use of certain types of woods like: oak, cedar, mahogany, guayacan, among others, in order to accomplish a sustainable forest management which helps preserve the biological diversity that exists in the forests. For this, it’s necessary to mend the Forest Law, considering that a sustainable forest development not only depends of the States offices created to protect the forest, natural areas and wild life, it´s also the citizens responsibility to create conscience of the new reality that is happening throughout the world, being contamination, deforestation, droughts, extinction of flora and fauna the consequence of the inappropriate use of the resources that so generously nature has given to all human beings